MicroRNAs in Development - Danielle Maatouk; Brian D. Harfe (The Scientific World Journal, 2006)
Over 10 years ago, the lab of Victor Ambros cloned an unusual gene, lin-4, which encodes two small RNA transcripts[1]. In the past few years, hundreds more of these tiny transcripts, termed microRNAs (miRNAs), have been uncovered in over a dozen species. The functions of the first two miRNAs, lin-4 and let-7, were relatively easy to identify since they were found in forward genetic screens in Caenorhabditis elegans[1,2,3]. However, uncovering the functions of the growing list of miRNAs presents a challenge to developmental biologists. This review will describe our current understanding of how miRNAs regulate gene expression and will focus on the roles these noncoding RNAs play during the development of both invertebrate and vertebrate species.